Grupo pequeño de personas. (UNED, 2023)
Aparece de izquierda a derecha Rodrigo Barrantes Echavarría, Nidia Lobo Solera, María Isabel Esquivel Soto, Adib Abdallah Arrieta, Luis Guillermo Carpio Malavassi, afuera del edificio A